Earthquakes and coastal archaeology: Assessing shoreline shifts on the southernmost Pacific coast (Chonos Archipelago 43°50′-46°50′ S, Chile, South America) - Reyes, Omar; Mendez, Cesar; San Roman Bontes, Manuel Julio; Francois, Jean-Pierre (My University, 2018)
Subduction, isostatic rebound, and changes in global sea levels, combined with the last glaciation, have shaped the geography of the channels of Western Patagonia. Current archaeological research in this area includes some ten sites that allow us to characterize the occupation of this territory by marine hunter-gatherers. The studied archaeological sites also inform about the various geomorphological changes that the coastline has undergone. Archives dating back six thousand years ago and archaeological contexts yield new insights about the location, distribution, and position of the shoreline and its changes over time. We present a set of data, including new sites and AMS radiocarbon determinations, which supports the hypothesis that landforms have risen or subsided, and provide the bases for a working model in which archaeological ages can inform the chronology of changes in the region's coastal morphology. This paper suggest that human occupations between 6200 and 4400 cal BP recorded on high terraces of the Guiatecas Archipelago indicate higher local sea-levels, while the sites immediately on the waterfront are 2000 years younger. On the other hand, sites younger than 3300 cal BP on the modern coastline of the Chonos archipelago undergo permanent shaping, mainly due to local tectonics affecting vertical movement. Considering previously published and new data provided in this paper, we suggest preliminary uplift rates between 0.57 and 5.42 m/ka for the Guaitecas Archipelago, 0.31-1.48 m/ka for the northern sector of the Chonos Archipelago, and 0.85 m/ka in the central sector. (C) 2016 Elsevier Ltd and INQUA. All rights reserved.
Keywords: coastal archaeological sites; holocene sea-level change; earthquakes; shell middens; western patagonia channels